Medidas de adequação ambiental para indústria de leite e derivados, como requisito para gestão ambiental - Sobrinho, Flavia Fernandes [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
The society continues demonstrating its need regarding the products and services, even though it becomes increasingly value the protection of the environment. In this context, environmental management is defined as a management method that emphasizes to continuously improve results and promote sustainable development. Moreover it has as a tool the laws which provide the benchmarks and mechanisms for companies to adapt their activities in such a way that does not alter the quality of the environment. In this sense, in order to propose improvements to a dairy aiming their environmental suitability, a present study was prepared by following the production activities of the enterprise, the raising of standards and applicable legal requirements and environmental assessment for the preparation of an array of aspects and impacts with the task of identifying the most significant according to MOREIRA (2006). The results indicated that some of the impacts of high relevance are related to the generation of wastewater and solid waste, which do not have treatment and / or proper disposal and indeed require intervention for their suitability. Through, these results were drawn up proposals for actions conformation. In addition, they were proposed meeting the requirement for health and safety at work, in accordance with the standard regulations. This study has the function, therefore, propose to the company in question, an environmental management plan that ensures the protection of the environment and health of employees and consequently the improvement of production processes and products

A sociedade continua evidenciando sua necessidade quanto a produtos e serviços, porém passa a valorizar cada vez mais a proteção do meio ambiente. Neste contexto, a gestão ambiental se define como um método de gerenciamento que visa à melhoria contínua dos resultados e promova o desenvolvimento sustentável. Dessa forma, possui como ferramenta as legislações, que fornecem os valores de referência e os mecanismos para que as empresas adaptem suas atividades, de tal modo que não alterem a qualidade do meio ambiente. Neste sentido, com o objetivo de propor melhorias para um laticínio, visando sua adequação ambiental, o presente trabalho foi elaborado por meio do acompanhamento das atividades de produção do empreendimento, o levantamento de normas e requisitos legais aplicáveis e diagnóstico ambiental para elaboração de uma matriz de aspectos e impactos com a função de identificar os mais significativos, de acordo com Moreira (2006). Os resultados indicaram que alguns dos impactos de alta relevância estão relacionados com a geração de efluentes e resíduos sólidos, os quais não possuem tratamento e/ou disposição adequada e por isso necessitam de intervenção para sua adequação. Através destes resultados foram elaborados propostas de ações de conformação. Também foi proposto o atendimento aos requisitos quanto à saúde e segurança no trabalho, de acordo com as Normas Regulamentadoras. Este trabalho teve a função, portanto, de propor à empresa em questão, um plano de gestão ambiental que garanta a proteção do meio ambiente e da saúde dos seus funcionários e por consequência a melhoria dos processos produtivos e produtos
Keywords: Engenharia ambiental; Gestão ambiental; Desenvolvimento sustentável; Impacto ambiental; Laticínios - Aspectos ambientais; Proteção ambiental